Answer:
B (√a*x+√c)^2=0
Step-by-step explanation:
It can be helpful to look a the expanded form of each of these factoring patterns.
A (ax+√c)^2=0 ⇒ a^2x^2 +2a√c*x +c = 0
B (√a*x+√c)^2=0 ⇒ ax^2 +2√(ac)*x +c = 0
C (√a*x+c)(√a*x-c)=0 ⇒ ax^2 -c^2 = 0
D (ax+√c)(ax-√c)=c ⇒ a^2x^2 -c = c
If 'a' and 'c' represent the coefficients in the given equation, then choices A, C, and D can be eliminated. The expanded forms of those end up with a^2 and/or c^2 as coefficients, not 'a' and 'c'.
Choice B is the only sensible one, and fits the given equation.
a = 1, c = 49 ⇒ √a = 1, √c = 7
x^2 +14x +49 = (x +7)^2 = 0 . . . . . factored using Pattern B